Optimalisasi Posyandu Lansia Melalui Pemeriksaan Kesehatan di Desa Sumare Kabupaten Mamuju - Nasrullah Nasrullah; Armidayanti Armidayanti; Dewarawati Patandean; Kadek Dwi Suarjana; Asnuddin Sokong; Nurfadhillah Salahuddin; Muh. Furqan; Wenry Deston Latif (STIKES Marendeng Majene, 2025)
Health check-ups are crucial, especially for the elderly, as they are susceptible to disease. Therefore, this community service activity aims to support and strengthen the existence of the elderly integrated health post (Posyandu) by providing free health check-ups, education on healthy lifestyles, and assistance in monitoring the health of the elderly. The methods used included free physical examinations, health consultations, health education, vitamin distribution, and health recording and monitoring. This activity involved a team of lecturers, students, medical personnel, and community health workers who provided health services to the community. The results provided information on public health, focusing on the elderly. Physical examinations included height, weight, blood pressure, blood sugar, and uric acid levels. Providing health education is expected to be beneficial in helping the community, especially the elderly, improve their health. In conclusion, the Posyandu activities for the elderly were well-implemented and received a positive response from the community, particularly the elderly.